Design and Analysis of Sharpened CIC Filter - Singhal, Anirudh (My University, 2015)
Cascaded-integrator-comb (CIC) filter is the simplest decimation filter. However, its magnitude response has a high pass-band droop, which is not tolerable in various application. CIC compensator is a technique used for the reduction of the droop.CIC filter is an FIR structure, which consists of cascaded integrator stages working at the higher sampling rate and the same number of comb stages working at the low sampling rate. A number of cascaded integrator comb pairs are chosen to meet the design requirements for aliasing orimaging errors. Although, the CIC filters can implement decimation and interpolationefficiently in the hardware for a wide range of rate change factors, yet CIC filter responseis lacking in a flat pass-band response and better transition bandwidth. To circumventthese problems, a compensation FIR filter can be employed in cascade with the CIC filterto provide frequency correction as well as spectrum shaping. The main aim of this work is to improve the magnitude response of CIC filters and also solve the passband droop problem. For improving the passband and the transition band features of the CIC filter and for improving the performance of CIC filter there are many techniques such as compensation filter cascaded with CIC filter, sharpening technique, polyphase decimation FIR filter to achieve wide broadband compensation of the CIC filter and maximally-flat based compensator filter. Thedroop can be reduced by modifying the original CIC structureor by connecting an additional filter called CIC compensator incascade with the CIC decimator.The former approach is basedon a technique called sharpening.In recent years, several methods forthe design of CIC compensators have been developed and now compensation is combined with a sharpening technique. In this dissertation, we implemented the CIC compensation filter that is based on maximally flat criterion. Also study the maximally flat criterion and different technique to improve CIC filter response. The method is based on the minimization of error function in the least-square sense. The main goal of this CIC filter’s design is to explain the wideband compensation as well as to efficientlyimplement the compensator filters. Additionally, the multiplierlessimplementation is proposed.In this method Leibniz rule is used but when solved the set of linear equation to get the iv filter’s coefficients for high order of FIR filter order, complexity increase in solving the equations. After that we proposed a new design of CIC compensator filter that is different from the existing one. This design is also based on maximally flat criterion but will use different technique to get filter coefficients and improve the passband droop problem for same order of FIR filter. The compensator’s coefficients are obtained by solving a linear system of equations. In this method Bernoulli numbers and Riemann zeta function are used and to get filter’s coefficients linear system of equation in matrix form is used. Due to this complexity is reducing to solve the equations.Later, we compared the results of new design with different orders with the previous design of CIC compensator. Then we found that results of new proposed design are far better than the existing one, which makes it less complex and more efficient. The proposed method gives the better magnitude response of compensated CIC filter.
M.E. (Wireless Communication Engineering)
Keywords: CIC Filter; ECED